Immunomodulator Activity of Effervescent Granule of Wualae Fruit (Etlingera elatior (Jack) R.M. Smith) Based on Specific Phagocytic Activity - Adryan Fristiohady; Wa Ode Siti Zubaydah; Wahyuni Wahyuni; Mirda Mirda; Saripuddin Saripuddin; Rina Andriani; La Ode Muhammad Julian Purnama; Sahidin Sahidin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The previous study reported that Etlingera elatior (Wualae) has activity as immunostimulant with dose at 300 mg/kg BW and 400 mg/kg BW. Formulating natural product into effervescent granule (GE) can increase practicality and interest to consume traditional medicine. This study aims to investigate the immunostimulant activity of Wualae ethanolic extract in the effervescent granule. Wualae was macerated with ethanol then formulated into effervescent granule at dose 300 mg/kgBW and 400 mg/kgBW. Formulations were evaluated. Animals were divided into 4 groups and treated with: group I (positive control); group II (negative control); group III (GE dose at 300mg/kgBW); and group IV (GE at dose 400mg/kgBW) for 7 days and at days 8, groups were infected by Staphylococcus aureus intraperitoneally. Immunostimulant activity was measured by calculating the Specific Phagocytic Activity (SPA) of macrophage. Data collected from the evaluation and measurement of the SPA then analyzed using SPSS. Results from the evaluation were considered good except the moisture content of effervescent granule. Results from SPA was found that effervescent granule at dose 300 mg/kgBW and at dose 400 mg/kgBW have 26.33% and 32.5% consecutively with significance 0.02 (p<0.05). Thus, effervescent granule has comparable phagocytosis activity with positive control.